Վարդանանց պատերազմն ըստ Դ. Դեմիրճյանի - Ա. Գ. Դոլուխանյան (ՀՀ ԳԱԱ հրատ.)
В 1943 г. в журнале ”Советакан граканутюн” (”Советская литература”) была опубликована статья Д. Демирчяна ”Война Вардананц”, в которой, основываясь на данных историков V в. Егише и Лазаря Парпеци, он попытался в новом свете представить историко-психологический аспект войны Вардананц. Д. Демирчян усматривал в этой войне божественный замысел. 1943, Demirchian submitted a paper on Vardanants War to the monthly review ”Sovetakan Grakanutiun” (” Soviet Literature”), in which he attempted to cast a new light on the historical-psychological aspects of the mentioned war. Unlike Yeghishe and L.Parpetsi, Demirchian did not regard the victory gained by the Armenians nation as moral, but considered it to be a military one that concluded Armenian national liberation movement. D. Demirchian saw a divine intervention in Vardanants war.
Keywords: History; Literature; Language and Literature; D History